Therapeutic Bronchoscopy in Benign Central Airway Obstruction - Mia Elhidsi; Budi Prasetio Nugroho; Wahju Aniwidyaningsih (Jurnal Respirologi Indonesia, 2022)
Benign central airway obstruction (BCAO) may occur in patients with post-intubation, tracheostomy, tuberculosis and non-tuberculosis infections, tracheal wall abnormalities, endobronchial benign tumors, vascular abnormalities, benign thyroid tumors and external mechanical compression. The management of BCAO is based on the underlying disease and requires multidisciplinary joint decisions from interventional pulmonology, thoracic surgery, radiology and anesthesia. Therapeutic bronchoscopy for the management of BCAO emergencies includes balloon dilation, stents and lasers.